Identification of the Neurospora crassa mutation un-10 as a point mutation in a gene encoding eukaryotic translation initiation factor 3, subunit B. - Matthew Kinney; Aric Wiest; Michael Plamann; Kevin McCluskey (Fungal Genetics Reports, 2009)
The Neurospora crassa temperature-sensitive mutant known as un-10 has been shown by a map-based complementation approach to be a single nucleotide change in the open reading frame of the eukaryotic translation initiation factor 3b (NCU02208.3).